India's rice export restrictions and BIMSTEC countries: Implications and recommendations - Kamar, Abul; Roy, Devesh; Pradhan, Mamata; Saroj, Sunil (International Food Policy Research Institute, 2023)
The Bay of Bengal Initiative for Multi-Sectoral Technical and Economic Cooperation (BIMSTEC) brings together five South Asian countries (Bangladesh, Bhutan, India, Nepal, and Sri Lanka) and two Southeast Asian countries (Myanmar and Thailand). Recent events have raised global concerns on food security, including for BIMSTEC countries; these events include Russia’s withdrawal from the Black Sea Grain Initiative with Ukraine, India’s prohibition on the export of non-basmati white rice, and its 20 percent export duty on parboiled rice. This policy note spells out the likely impact of one of these events, that is, India’s restrictions on rice exports to its fellow BIMSTEC nations. Trade moves food from surplus to deficit regions and hence is crucial for maintaining a stable food supply. Historically, the global supply of cereals has been stable (Bradford et al. 2022); this implies that trade (or the lack of it) can be directly mapped onto area-specific food insecurity. At the same time, shocks leading to trade disruption can pose serious challenges, particularly for countries with high import penetration in food.